Pengaruh Motivasi dan Komitmen terhadap Kinerja Relawan pada Dompet Dhuafa Lampung - Tantya, Meiby Carina; Sari, Liana; Muda, Rini Agustin; Asmoro, Galih; Murcitaningrum, Suraya (Teewan Journal Solutions, 2026)
This study investigates how motivation and commitment influence the performance of volunteers at Dompet Dhuafa Lampung. A quantitative method with an associative design was employed to examine the relationships among the variables under study. The research involved 50 active volunteers as both the population and sample, selected through a saturated sampling approach. A questionnaire-based survey was administered to gather the necessary data, which were subsequently processed using multiple linear regression analysis along with t-test and F-test procedures.The findings revealed that motivation and commitment, when considered together, exerted a statistically significant impact on volunteer performance, as evidenced by an F-test significance value of 0.000, which falls well below the 0.05 threshold. When examined individually, each variable likewise demonstrated a meaningful influence on volunteer performance. Furthermore, the coefficient of determination stood at 0.534, suggesting that approximately 53.4% of the variation in volunteer performance can be attributed to the combined effect of motivation and commitment. These results lead to the conclusion that both motivation and commitment serve as critical determinants in enhancing the overall performance of volunteers.